14 lessons from the story of Qabil and Habil - Omer, Spahic (IIUM Today, 2019)
The article is about 14 lessons that can be gleaned from the story of Prophet Adam’s two sons: Qabil (Cain) the wicked one and the murderer, and Habil (Abel) the righteous one and the victim. The story is presented in the Qur’anic chapter al-Ma’idah (the Table Spread with Food), verses 27-31. The story is given in several contexts pertaining to the affairs of the Jews, Christians, and Prophet Muhammad (pbuh) and his followers. The substance of the lessons is that Islam is the only religion with Allah (Alu ‘Imran, 19). No other alternative is acceptable (Alu ‘Imran, 85). Therefore, every messenger or prophet of Allah, from Adam to Muhammad (peace and blessings be upon them all), was asked to convey to his people that there is no god or deity except Allah, and that He alone must be worshipped (al-Anbiya’, 25). All other religions represent either distorted versions of Islam, or man-concocted superstitious faiths and creeds. Polytheism, atheism, and agnosticism as the latter’s twin, are the greatest spiritual crimes committed by humanity against their Creator and Master. Islam stands for ultimate truth which, in turn, transcends the variables of time and space dynamics. Obviously, sacrifice (qurban), both as an idea and ritual, was an aspect of Islamic worship during Adam’s time.